Components as processes: an exercise in coalgebraic modeling - Barbosa, L. S. (2000)
IFIP TC6/WG6.1. Fourth International Conference on Formal Methods for Open Object-Based Distributed Systems (FMOODS 2000) September 6–8, 2000, Stanford, California, USA